Sensory stimulations potentializing digital therapeutics pain control - Fougère, Maxime; Greco-Vuilloud, Juliette; Arnous, Chloé; Abel, Florence; Lowe, Chrissy; Elie, Valery; Marchand, Serge (Frontiers in Pain Research, 2023)
For the past two decades, using Digital Therapeutics to counter painful symptoms has emerged as a novel pain-relief strategy. Several studies report that DTx significantly diminish pain while compensating for the limitations of pharmacological analgesics (e.g., addiction, side effects). Virtual Reality (VR) is a major component of the most effective DTx for pain reduction. Notably, various stimuli (e.g., auditory, visual) appear to be frequently associated with VR in DTx. This review aims to compare the hypoalgesic power of specific stimuli with or without a VR environment. First, this review will briefly describe VR technology and known elements related to its hypoalgesic effect. Second, it will non-exhaustively list various stimuli known to have an hypoalgesic effect on pain independent of the immersive environment. Finally, this review will focus on studies that investigate a possible potentialized effect on pain reduction of these stimuli in a VR environment.